Community Structure of Seagrass Field in Litoral Zone of Leweung Sancang Garut Nature Reserve - Dimas Zulfadillah; Diana Hernawati; Diki Muhamad Chaidir (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Seagrass meadows or seagrass beds are one of the important components in coastal ecosystems. Seagrasses provide ecosystem services for various biota that live in it as well as components of the surrounding coastal ecosystems. The Sancang Nature Reserve is one of the coastal areas that has seagrass communities, and seagrass observation data is needed for reference to conservation strategies. This study aims to determine the condition of the cover and the structure of the seagrass community that fills the littoral zone of the Sancang Nature Reserve using the quadratic transect method, which was conducted from March 17 Ã¢â¬â 21, 2021. The data collected were seagrass species, species frequency, species cover and total cover, and the importance value index of species. Observations were made at 3 stations with an area of 100 m2 each along Ciporeang Beach, at each station 30 square transects with a size of 50 cm were placed, with 1 square transect divided into 25 grids measuring 10 cm. As well as the observation of environmental physical and chemical indicators. The results showed that the seagrass community in the research sites were overgrown by species Cymodocea rotundata and Thalassia hempricii which had a cover condition in the rich category with a percentage of 61.09%. Species densities were 117 i/m and 679 i/m, species closures were 36.95% and 25.63%, and the importance value index of species were 1.49 and 0.54. The difference was significantly influenced by physical indicators such as substrate structure and current velocity, while the chemical indicators at each station did not show a significant difference. Nutrient content data in the substrate at each station is needed to get more detailed conclusions about the factors that affect seagrass cover on the Sancang coast.